SUCCESSFUL TREATMENT OF JUVENILE GENERALIZED DEMODICOSIS WITH A SINGLE DOSE OF ORAL FLURALANER - R.M. Gowtham; R.Kavin (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Two non-descript puppies aged around three months old were presented with a history of erythematous skin and the presence of crusty lesions with intense pruritus around one week. Physical examination revealed generalized erythema and alopecia, crusty and scaly lesions on the forehead, periorbital area, nasal planum, and thorax regions in both puppies. Based on history, clinical signs and skin scraping examination findings, the cases were confirmed as juvenile generalized demodicosis and the puppies were treated with a single dose of oral fluralaner at the dose of 25 mg/kg body weight. The treatment resulted in excellent resolution of clinical signs and the puppies had an uneventful recovery.